FEATURES OF NUTRITIONAL HYGIENE IN CANCER DISEASES - G.F.Omonova, J.P.Omonov (Modern World Education: New Age Problems – New solutions, 2026)
According to WHO estimates, in 2018 cancer caused 9.6 million deaths worldwide, accounting for 30–60% of all deaths. Globally, the number of people diagnosed with tumor diseases is increasing every year. Currently, cancer treatment can be carried out using surgical methods, chemotherapy, radiation therapy, or their combination. To ensure the effectiveness of these treatment methods, adequate provision of essential macro- and micronutrients and vitamins for the patient’s body is of great importance [1,4].